Analisis potensi daerah sebagai upaya meningkatkan perekonomian daerah di Sumatera Bagian Selatan - Clara Ayu Monica; Taufiq Marwa; Anna Yulianita (Jurnal Ekonomi Pembangunan, 2017)
The objectives of this study were to identify and analyze the basic/leading sectors that have competitive advantages in each province, and to determine the regional typology and basic-sector priorities for regional development. The data used in this study were times series data in the period of 2010-2014. The data were analyzed by using LQ analysis, shift share, and Klassen typology. The result of this study indicated that each province had its own potentials in accordance with its conditions. The agricultural sector was the dominant basic sector in southern Sumatra for the five provinces had this basic sector; while other sectors varied by province. Only the Province of Bengkulu had company services and educational services; besides, Bengkulu had the most basic sectors (9 basic sectors), namely agricultural sector with LQ value of (2.34), water supply (3.14), trade (1.02), transport (2.06), real estate (1.47), company services (1.39), administration (2.29), educational services (2.01), and health services (1.40). The Province of Jambi was included in the fast-forward and fast-growing regional typology. Then, South Sumatra, Bengkulu, Lampung and Bangka Belitung were in the fast-growing regional typology. Based on the research results, there should be government intervention in developing potential sectors to become leading sectors in the regions and in enhancing the economic growth and competitiveness of the regions in southern Sumatra